2015
DOI: 10.1111/jpim.12287
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and Horizontal Cross‐Ties: Benefits of Cross‐Hierarchy and Cross‐Unit Ties for Innovative Projects

Abstract: Social networks are an important driver for successful innovation, both at the individual level as well as the organizational level. Recent research has also shaped that networks within teams can enhance performance. Innovative project teams are embedded in an organizational context, however, and teams typically consist of people with expertise from diverse backgrounds, and from different units. Team members may have ties to other teams, business units, and hierarchical levels. Although it seems clear that suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 94 publications
0
27
0
Order By: Relevance
“…In this special issue, Aalbers, Dolfsma, and Leenders () present a case study of five new product development projects. They focus their analysis on the ties that project teams maintain throughout the company (to other teams or to management), and study whether these external ties support the innovative performance of the teams.…”
Section: Social Network and Innovationmentioning
confidence: 99%
“…In this special issue, Aalbers, Dolfsma, and Leenders () present a case study of five new product development projects. They focus their analysis on the ties that project teams maintain throughout the company (to other teams or to management), and study whether these external ties support the innovative performance of the teams.…”
Section: Social Network and Innovationmentioning
confidence: 99%
“…Additionally, Hansen (2002) argues that informal relations allow one to tap into new knowledge more easily. Informal relations provide the opportunity for information and knowledge to flow in both vertical and horizontal directions, contributing to the overall flexibility of the organization (Aalbers, Dolfsma and Leenders, 2014;Cross, Borgatti and Parker, 2002). Informally, individuals may be willing to exchange information and favours beyond what the organization has formally mandated them to do (Dolfsma, Van der Eijk and Jolink, 2009).…”
Section: Innovative Knowledge Transfer In Organizationsmentioning
confidence: 99%
“…Previous research has already shown that a focal firm (Firm A in the example) is in general likely to enjoy higher innovation capabilities because it can access nonredundant and heterogeneous knowledge from the otherwise disconnected firms in its ego network (Firms B, C, and D in the example) (Aalbers et al, 2016;Bonner and Walker, 2004;Burt, 2004;Knudsen, 2007;Operti and Carnabuci, 2014;Tortoriello and Krackhardt, 2010). However, focal firms are likely to differ when recognizing and deciding whether to acquire, integrate, and use the heterogeneous knowledge made available by bridging structural holes in their ego networks.…”
Section: Theory Developmentmentioning
confidence: 99%
“…It has also suggested that given today's increased market competition and rapidly changing technologies, many firms may not be capable of engaging in innovation with their own internal knowledge but may need external knowledge (Powell, Koput, and Smith-Doerr, 1996). Consistently, studies have suggested that firms can significantly benefit from bridging two or more otherwise disconnected firms in their ego networks (i.e., structural holes) as a potentially useful source of external knowledge for innovation (e.g., Aalbers, Dolfsma, and Leenders, 2016;Bonner and Walker, 2004;Burt, 2004;Knudsen, 2007). These studies also suggested that this is because the disconnected firms are likely to offer the firms bridging them heterogeneous and nonredundant knowledge that is conducive for innovation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation